How to Reduce Moral Hazard Crisis in Business: Study from Indonesian's Pesantren - Rifai, Khamdan (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
This empirical study report on Pesantren (Islamic Boarding School) aimed to explore how to manage the pesantren enterprise. It deals with the pesantren phenomenon but from a different angle. A philosophical stream of Al Hikam taught Kasab (human must fill their needs earnestly) and Tajrid (life attitude doesn't make bustle about solely worldly pursuit). Those tasawuf concepts are reflected in pesantren's economic behaviour, which is believed to counter a business ethic crisis that began being popularized in the late 90s about the spiritual organization.